Durability and extent of protection of SARS-CoV-2 antibodies among patients with COVID-19 in Metro Manila, Philippines - Gonzales, Ma. Liza Antoinette M.; Dans, Leonila F.; Tan-Lim, Carol Stephanie C.; Uy, Elenore; Cutiongco-dela Paz, Eva; Sulit, Maria Vanessa V.; Alejandria, Marissa M.; Lansang, Mary Ann D.; Dans, Antonio L.; Dator, Melissa A.; Cordero, Cynthia P.; Pardilla, Gina F. (Frontiers in Immunology, 2023)
Introduction: Information on the magnitude and durability of humoral immunity against COVID-19 among specific populations can guide policies on vaccination, return from isolation and physical distancing measures. The study determined the durability of SARS-CoV-2 antibodies after an initial infection among Filipinos in Metro Manila, Philippines, and the extent of protection SARS-CoV-2 antibodies confer against reinfection. Methods: We conducted a cohort study to monitor the antibody levels of patients diagnosed with COVID-19. Receptor-binding domain (RBD)-specific antibodies were measured at Days 21, 90, 180, 270 and 360. Antibody levels were reported as geometric mean titers (GMT) with geometric standard deviation (GSD). Differences in GMT were tested using Friedman test and Kruskal Wallis test, with Bonferroni multiple comparisons procedure. Adjusted hazard ratios on the development of probable reinfection were estimated using Cox proportional models. Results: There were 307 study participants included in the study, with 13 dropouts. Study participants received SARS-CoV-2 vaccines at varying times, with 278 participants (90.5%) fully vaccinated by the end of study. The GMT of the study cohort increased over time, from 19.7 U/mL (GSD 11) at Day 21; to 284.5 U/mL (GSD 9.6) at Day 90; 1,061 U/mL (GSD 5.3) at Day 180; 2,003 U/mL (GSD 6.7) at Day 270; and 8,403 U/mL (GSD 3.1) at Day 360. The increase was statistically significant from Day 21 to Day 90 (p<0.0001), Day 90 to Day 180 (p=0.0005), and Day 270 to Day 360 (p<0.0001). Participants with more severe initial infection demonstrated significantly higher antibody levels compared to those with milder infection at Day 21. Sixty-four patients had probable COVID-19 reinfection (incidence of 20.8%, 95% CI 16.4, 25.8%). The GMT of these 64 patients was 411.8 U/mL (GSD 6.9) prior to the occurrence of the probable reinfection. Majority (87.5%) were fully vaccinated. Antibody titers significantly affected the risk of developing reinfection, with adjusted hazard ratio of 0.994, 95% CI 0.992-0.996, p<0.001. Conclusion: Antibody levels against SARS-CoV-2 increased over a one-year follow-up. Higher antibody levels were observed among those with more severe initial infection and those vaccinated. Higher antibody levels are associated with a lower risk of probable reinfection.